Covid-19 is real! / Norashikin Mohd Mokhtar - Mohd Mokhtar, Norashikin (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
What is it? Where does it come from? And how? But yes, Covid-19 is real! It happened, and I have experienced the fear of losing a loved one myself. It was the second wave of Covid-19 when my father and mother-in-law were hospitalized for Covid-19. I cannot tell what or how I feel. The feeling is unexplainable. It was a rush of fear that haunted us; 'the family members'. Have you ever waited for a call from the hospital? Yes, it is like a husband waiting for the news from the wife from the delivery room. But this time it is a bit different. First, we would never have thought that a person who rarely goes out would be infected with the virus, and the first symptom was a high fever that lasted for a few weeks. Ayah was a healthy person and rarely sick. Even when he is down with a fever or flu, he would not take medication and refused to go to the clinic. We were so worried that we just had to call a chartered ambulance nearby as he had no strength left to move. A few hours later, we received a call from my husband who had accompanied him in the ambulance. The news was shocking to all of us at home when he mentioned that his father had tested positive Covid-19 for RTK and had to take a PCR test. Can you imagine how we felt? What did we think? So, at home we started asking each other questions. Where has he been before? When was the last time he went out, and all sorts of questions were asked until we were at a loss.